Marketing Strategy Of Roffee's Dessert In Order To Improve sales Performance - Zam Harira, Emil; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract. Roffee’s Dessert was established in Bandung City since November 2013. This company sells a new kind of dessert called soft pudding. The difference is it has a really smooth texture that will melt in the mouth.  Compared to the competitors Roffee’s Dessert has some advantages that are offer a high quality product with an affordable price. As a startup company Roffee’s Dessert encountered several issues which are low distribution, low brand awareness, and store location that is not strategic. All these issues affect the sales performance of Roffee’s Dessert. In order to solve the issues, the author analyzes the company’s condition using Porter’s 5 Forces, 5P’s Marketing Mix, and Competitor analysis. After analyzing the condition of the company, it is found that the root cause of the problems are there is no well planned marketing program and all the activities are still done by the owner alone. In order to generate the strategies, the author use SWOT analysis and TOWS matrix. After that STP process is used to as a tool to create the 5P’s marketing mix that is derived from strategies generated in TOWS matrix. The solutions proposed in this thesis is in the form of new 5P’s marketing mix that will attract customers, widen distribution, improve branding, and increase brand awareness. The proposed solutions for are open new store, improve value proposition, redesign the packaging, create marketing plan, make promotion programs, and hire marketing employees to increase the number of consignment places. All the solutions are planned to be implemented in 12 months. By implementing all of the solutions, it is expected that after 12 months all the issues that currently encuntered by the company will be resolved and the sales performance will be improved. Keywords: Dessert, Food, Marketing strategies, Marketing Mix